2022
DOI: 10.1111/andr.13353
|View full text |Cite
|
Sign up to set email alerts
|

Follicle‐stimulating hormone effectiveness in male idiopathic infertility: What happens in daily practice?

Abstract: Objectives: To assess the effectiveness of follicle-stimulating hormone (FSH) administration in male idiopathic infertility in a clinical setting. Methods:A retrospective real-world study was carried out, including all consecutive FSH-treated infertile men attending the Andrology Unit of Modena (Italy) from June 2015 to May 2022. Medical history, physical and andrological examinations, hormonal and seminal parameters, therapeutic management and pregnancy data were collected. The primary endpoint was the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 64 publications
(130 reference statements)
0
10
0
Order By: Relevance
“…The potential FSH efficacy in idiopathic infertility has been confirmed by recent real-world data analyses, 11,18 providing new relevant information directly from the clinical practice. 44 A recent study from our group 18 showed a positive FSH effect both in terms of pregnancy rate (one preg-nancy in every four men treated), and in terms of sperm quality improvement (particularly referred to sperm number).…”
Section: The Use Of Gonadotropins In Male Idiopathic Infertilitymentioning
confidence: 84%
See 4 more Smart Citations
“…The potential FSH efficacy in idiopathic infertility has been confirmed by recent real-world data analyses, 11,18 providing new relevant information directly from the clinical practice. 44 A recent study from our group 18 showed a positive FSH effect both in terms of pregnancy rate (one preg-nancy in every four men treated), and in terms of sperm quality improvement (particularly referred to sperm number).…”
Section: The Use Of Gonadotropins In Male Idiopathic Infertilitymentioning
confidence: 84%
“…The potential FSH efficacy in idiopathic infertility has been confirmed by recent real-world data analyses, 11,18 providing new relevant information directly from the clinical practice. 44 A recent study from our group 18 showed a positive FSH effect both in terms of pregnancy rate (one preg-nancy in every four men treated), and in terms of sperm quality improvement (particularly referred to sperm number). 18 In this study, we evaluated the efficacy of FSH used at the same dose applied to hypogonadotropic hypogonadism routinely used in clinical practice, showing an overall efficacy higher than that in in meta-analysis, but still perfectible, confirming the need to change the aim of FSH administration, shifting from "replacement" to "overstimulatory" treatment.…”
Section: The Use Of Gonadotropins In Male Idiopathic Infertilitymentioning
confidence: 84%
See 3 more Smart Citations